Dynamics of Change in Customary Actor Authority After Determining the Status of Indigenous Villages in Siak Regency - Setiawan, Husni (Komunitas, 2019)
This study discusses the status of adat which has the power of formal law which gradually impacts on the addition and strengthening of political rights of traditional leaders. This phenomenon occurs in the Sakai Minas Traditional Village, Siak Regency. The community of the traditional village made a rule that the chief (Village Chief) must come from ethnic Sakai or who have blood ties with the Sakai community. On the other hand, there is a dichotomy of the political rights of people outside of Sakai Ethnicity. This study aims to analyze the strengthening of the authority of indigenous actors in Kabupaten Siak. This study uses a qualitative method. Analysis of data using emik based on the results of in-depth interviews and related documents. The results of the study showed that after the establishment of Sakai Minas Traditional Village status, customary actors experienced formal political authority (de jure) strengthening compared to before the establishment of traditional village status. Strengthening this authority comes from the interpretation of the Perda Kabupaten Siak No. 2 of 2015 concerning the Establishment of Traditional Villages.